Problems in universalization of primary education in Pakistan - Shahinshah Babar Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2010)
"Education for all" is a global slogan and government of Pakistan is committed to achieve the goal of Universalization of primary education. For this government is establishing new schools in remote areas so that more and more children can get access to school. Public-private partnership and collaboration with non-government organizations are the steps to attain the level of Universalization of primary education. Government is trying to make schools attractive for children, and is introducing schemes to attract parents as well. There are number of problems like poverty, ignorance, low quality teaching, which affects the government efforts. The aim of the study is to highlight the problems in universalization of primary education in Pakistan. A questionnaire was developed on five point Likert scale for knowing the opinion of teachers about the problems in the universalization of primary education. Each statement of the questionnaire was checked by using chi-square technique. It was found that poverty, lack of awareness about importance of education, cultural values are the main problems in achieving universalization of primary education. On the basis of findings it is recommended that awareness about education may be created among the parents, Public schools play their role in decreasing the dropout rate, School Curriculum may design as which match the work place, teachers may be appointed in the far flung areas, Local Community may be involved. It is also considered by people that public institutions are not catering quality education, this notion may be abolished.
Keywords: 330; Primary education; universalization; Pakistan